Why and how to select a local porcine breed: the case of the Cinta Senese - Franci O.; Gandini G.; Bozzi R. (5. International Symposium on the Mediterranean Pig, 2007)
In the eighties the Cinta Senese breed was on the brink of extinction and experienced high inbreeding rates. In this regard the current programme for management of inbreeding and genetic variation is presented. No selection programmes are currently implemented in the Cinta Senese, however, if the current positive demographic trend continues, the need to identify selection objectives and strategies will emerge. The second part of the paper discusses how possible selection objectives must take into account breed characteristics and market trends. Both reproductive (number of teats and litter size) and productive traits (growth rate and carcass composition) are considered. Genetic parameters, as well as the inbreeding effect, are presented. However, besides the need for more investigations on growth and meat quality, the question of which selective objectives should be considered remains open because no clear trends in the market can be detected today. In fact we observe parallel interests for intensive and extensive farming and the market seems to be willing to continue to valorise fat as well as lean cuts.
5. International Symposium on the Mediterranean Pig, 2004/09/16-19, Tarbes (France)